Plasma Metabolomics Reveals Pathogenesis of Retained Placenta in Dairy Cows - Li, Yuqiong; Zhao, Zhengwei; Yu, Yang; Liang, Xiaojun; Wang, Shengyi; Wang, Lei; Cui, Dongan; Huang, Meizhou (Frontiers in Veterinary Science, 2021)
The complex etiology and pathogenesis of retained placenta (RP) bring huge challenges for researchers and clinical veterinarians in investigating the pathogenesis and treatment schedule. This study aims to investigate the pathogenesis of retained placenta in dairy cows by plasma metabolomics. As subjects, 10 dairy cows with retained placenta and 10 healthy dairy cows were enrolled according to strict enrollment criteria. Imbalanced antioxidant capacity, reduced Th1/Th2 cytokine ratio, and deregulation of total bilirubin (T-bil), alkaline phosphatase (ALP), and reproductive hormones were shown in dairy cows with retained placenta by detecting biochemical indicators, oxidation and antioxidant markers, and cytokines in serum. Plasma metabolites were detected and analyzed by an LC-MS system coupled with multivariate statistical analysis software. A total of 23 potential biomarkers were uncovered in the plasma of dairy cows with RP. The metabolic pathways involved in these potential biomarkers are interconnected, and the conversion, utilization, and excretion of nitrogen were disturbed in dairy cows with RP. Moreover, these potential biomarkers are also involved in the regulation of antioxidant capacity, inflammation, and autocrine or paracrine hormone. All of these findings suggest that an imbalance of these potential biomarkers might be responsible for the imbalanced antioxidant capacity, reduced Th1/Th2 cytokine ratio, and deregulation of reproductive hormones in dairy cows with RP. The regulation of metabolic pathways involved in these potential biomarkers represents a promising therapeutic strategy for RP.